A molecular-assisted investigation of diversity, biogeography and phylogenetic relationships for species of Neoptilota and Ptilota (Wrangeliaceae, Rhodophyta) reported along Canadian coasts. Issue 1 (1st January 2017) - Bruce, Meghann R.; Saunders, Gary W.
Abstract: Traditional morphology-based investigations of the red algal genera Neoptilota and Ptilota (Wrangeliaceae, Rhodophyta) have struggled to provide accurate accounts of diversity, distribution and evolutionary relationships for the species reported along Canadian coasts. Consequently, there is much disagreement and taxonomic uncertainty surrounding several species within these genera. To resolve these issues we conducted a molecular-assisted investigation that included both a DNA barcode survey (COI-5P), as well as the first multigene (COI-5P, psaA, rbc L) phylogenetic analyses for these genera. To compare our taxonomic results with a previous investigation we also sequenced psbA for select species. Our phylogenetic analyses indicated that current taxonomic perspectives among members of these genera were incorrect, as the generitypes for Neoptilota and Ptilota resolved together in a lineage that also included Psilothallia dentata, with the generitype for Plumaria weakly resolved as sister to all of the previous taxa. Synonymy of Neoptilota with Ptilota was proposed, as was the transfer of Psilothallia dentata to this genus. Additionally, our molecular analyses have indicated that diversity was previously underestimated for this complex. Whereas we uncovered no differences for the Atlantic flora relative to recent studies, in the northeast Pacific we considered Ptilota californica var. californica to be synonymous with P. densa and we expanded P. filicina to include specimens previously assigned to P. californica var. β concinna . We further failed to confirm the presence of P. serrata and recorded six additional species in British Columbia: reinstatement of P. tenuis ; P. gwaiihaanasica sp. nov .; P. haidarum sp. nov .; P. pseudohypnoides sp. nov .; P. sloanii sp. nov .; and, P. subita sp. nov . The implications of the taxonomic changes proposed here are discussed.